PELAKSANAAN DISIPLIN KERJA PEGAWAI DI DINAS KEBUDAYAAN DAN PARIWISATA KOTA PEKANBARU - Aldo Trinanda; Abdul Sadad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Employee discipline is an important factor that greatly influences the success of government organizations. Civil Servants (PNS) will not be able to take responsibility for their work if they are not disciplined by the rules that apply. This study has used government management theory and the concept of work discipline with fundamental analysis on compliance with regulations, effective work, corrective action, timely attendance and the ability to finish work on time. Inhibiting factors in the implementation of employee discipline consist of internal factors (competence, work experience, technology, management systems, compensation, leadership, work enthusiasm), internal factors greatly influence employees in the Discipline in the implementation of work discipline, so they must be able to become more employees discipline in accordance with existing regulations. external factors (economic, cultural, religious), these external factors affect every employee in the Disparbudpar in carrying out discipline, in this case internal and external factors must go hand in hand to make employees become more disciplined Keywords: Employees, Work Discipline, Performance Targets and Government Management